CARBONYIS FROM SOME COMMERCIALLY IMPORTANT FISHES AND SHELL FISHES IN TROPICAL WATERS - AMMU, K; NAIR, P. G VISWANATHAN; DEVADASAN, K (Fishery Technology, 2017)
Results of a preliminary study of the hexane extractable carbonyls from three fish and one shell fish are reported. Volatile carbonyls that can be isolated from oil sardine by distillation at different temperatures in air or nitrogen atmosphere were also studied. Carbonyls were converted to their 2:4 dinitro phenyl hydrozones. These were fractionated by column chromatography and the different fractions were analysed by capillary gas chromatography. The data show wide variations in the content of different carbonyls in different fishes. Carbonyls in distillates from muscle water homogenates of oil sardine showed some differences from the carbonyls extracted with hexane from the same fish. More data is necessary to correlate the carbonyls with the characteristic flavour of each fish.